Evidence of predisposing epimutation in retinoblastoma. Issue 2 (26th November 2018) - Gelli, Elisa; Pinto, Anna Maria; Somma, Serena; Imperatore, Valentina; Cannone, Marta G.; Hadjistilianou, Theodora; De Francesco, Sonia; Galimberti, Daniela; Currò, Aurora; Bruttini, Mirella; Mari, Francesca; Renieri, Alessandra; et al.
Abstract: Retinoblastoma (RB), which represents the most common childhood eye cancer, is caused by biallelic inactivation of RB1 gene. Promoter hypermethylation is quite frequent in RB tissues but conclusive evidence of soma‐wide predisposing epimutations is currently scant. Here, 50 patients who tested negative for RB1 germline sequence alterations were screened for aberrant promoter methylation using methylation‐specific MLPA. The assay, performed on blood, identified a sporadic patient with methylation of CpG106, absent in parents' DNA. Bisulfite pyrosequencing accurately quantified CpG methylation in blood DNA (mean ∼49%) and also confirmed the aberration in DNA isolated from oral mucosa although at lower levels (mean ∼34%). Using a tag‐SNP, methylation was demonstrated to affect the maternal allele. Real‐time qPCR demonstrated RB1 transcriptional silencing. In conclusion, we documented that promoter methylation can act as the first "hit" in Knudson's model. This mosaic epimutation mimics the effect of an inactivating mutation and phenocopies RB onset. Abstract : RB1 promoter hypermethylation is quite frequent in RB tissues but evidence of soma‐wide predisposing epimutations is currently scant. Here, methylation of CpG106 has been identified in a sporadic RB patient. Bisulfite pyrosequencing quantified CpG methylation in blood DNA (∼49%) and confirmed the aberration in oral mucosa DNA although at lower levels (∼34%). Methylation affects the maternal allele and causes RB1 transcriptional silencing. In conclusion, we documented that promoter methylation mimics the effect of an inactivating mutation and phenocopies RB onset.